2020
DOI: 10.1007/s11292-020-09439-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of brain injury on within-individual changes in moral disengagement: implications for criminal and antisocial behavior

Abstract: Objectives The current study aims to further unpack the link between head injury and criminal behavior by examining the association between brain injury and changes in moral disengagement. Methods The current study uses the Pathways to Desistance study (N = 1354) to estimate a series of longitudinal cross-lagged dynamic panel models to examine within-individual changes in moral disengagement across the study period. Results The results revealed that moral disengagement decreased over time, but sustaining a hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…Second, the current study examines a jail cohort. This extension of previous research is important, as few studies have systematically examined TBI within jail populations (Glover et al, 2018;Slaughter et al, 2003), instead focusing on prisons (Farrer & Hedges, 2011) or specific at-risk samples (Schwartz, 2019;Schwartz et al, 2017Schwartz et al, , 2020. Important differences between jail and prison populations have been previously documented , indicating that findings from the existing literature may not directly map onto other incarcerated populations.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the current study examines a jail cohort. This extension of previous research is important, as few studies have systematically examined TBI within jail populations (Glover et al, 2018;Slaughter et al, 2003), instead focusing on prisons (Farrer & Hedges, 2011) or specific at-risk samples (Schwartz, 2019;Schwartz et al, 2017Schwartz et al, , 2020. Important differences between jail and prison populations have been previously documented , indicating that findings from the existing literature may not directly map onto other incarcerated populations.…”
Section: The Current Studymentioning
confidence: 99%
“…Such studies typically report increases in behavior problems or criminal justice contact after sustaining a TBI, or a greater concentration of behavior problems among those who have sustained a TBI compared to those who have not Jackson et al, 2017;Ray & Richardson, 2017;Sariaslan, Lichtenstein, et al, 2016;Sariaslan, Sharp, et al, 2016;Schwartz et al, 2017Schwartz et al, , 2019. A smaller number of studies have reported increases in behavior problems and criminal justice contact stemming from within-individual changes in TBI over time (Schwartz, 2019;Schwartz et al, 2018Schwartz et al, , 2020. While these studies provide preliminary support for TBI as a causal influence, they do not effectively examine changes in criminal justice contact as a function of the timing of TBI, as they fail to consider prior contacts in a detailed manner.…”
Section: Traumatic Brain Injury As a Causal Influencementioning
confidence: 99%
“…Executive function deficits, especially increased impulsivity and aggression, are often implicated in criminal behavior, which provides a potential link between HI and criminal behavior (Moffitt 1993; Moffitt and Caspi 2001; Perron and Howard 2008; Vaughn et al 2014). Other deficits have been proposed, such as emotion regulation and moral reasoning, both of which can be impacted by the experience of an HI (Eslinger et al 2004; Schwartz, Fitter, and Jodis 2020; Tonks et al 2009)…”
Section: Hi and Crimementioning
confidence: 99%
“…Such studies typically report increases in behavior problems or criminal justice contact after sustaining a TBI, or a greater concentration of behavior problems among those who have sustained a TBI compared to those who have not Jackson et al, 2017;Ray & Richardson, 2017;Sariaslan, Lichtenstein, et al, 2016;Sariaslan, Sharp, et al, 2016;Schwartz et al, 2017Schwartz et al, , 2019. A smaller number of studies have reported increases in behavior problems and criminal justice contact stemming from withinindividual changes in TBI over time (Schwartz, 2019;Schwartz et al, 2018Schwartz et al, , 2020. While these studies provide preliminary support for TBI as a causal influence, they do not effectively examine changes in criminal justice contact as a function of the timing of TBI, as they fail to consider prior contacts in a detailed manner.…”
Section: Traumatic Brain Injury As a Causal Influencementioning
confidence: 99%
“…Second, the current study examines a jail cohort. This extension of previous research is important, as few studies have systematically examined TBI within jail populations (Glover et al, 2018;Slaughter et al, 2003), instead focusing on prisons (Farrer & Hedges, 2011) or specific at-risk samples (Schwartz, 2019;Schwartz et al, 2017Schwartz et al, , 2020. Without question, jail and prison populations have some overlap, as virtually all individuals are held in jails prior being transferred to prison.…”
Section: The Current Studymentioning
confidence: 99%